- #1

DBeckett91

- 6

- 0

Thanks in advanced for help on this, if I have gone wrong anywhere along the way please don't hesitate to point out my mistake(s).

Differatiate each question with respect to the variable.

s =(Ax^2-kx+w)/Ax+k

Quotient rule: ds/dx=((v*du/dx)-(u*dv/dx))/v^2

s = u/v

u = 8x^2-7x+125

v = 8x+7

du/dx = 8x^2-7x+125

= 16x-7

dv/dx = 8x+7

= 8

ds/dx=((v*du/dx)-(u*dv/dx))/v^2

ds/dx=((8x+7*16x-7)-(8x+7*8))/8x+7^2

ds/dx=((128x^2-56x+112x-49)-(64x^2-56x+1000))/8x+7^2

ds/dx=((128x^2-56x-49)-(64x^2-56x+1000)/8x+7^2

ds/dx=(64x^2+951)/8x+7^2

## Homework Statement

Differatiate each question with respect to the variable.

s =(Ax^2-kx+w)/Ax+k

## Homework Equations

Quotient rule: ds/dx=((v*du/dx)-(u*dv/dx))/v^2

## The Attempt at a Solution

s = u/v

u = 8x^2-7x+125

v = 8x+7

du/dx = 8x^2-7x+125

= 16x-7

dv/dx = 8x+7

= 8

ds/dx=((v*du/dx)-(u*dv/dx))/v^2

ds/dx=((8x+7*16x-7)-(8x+7*8))/8x+7^2

ds/dx=((128x^2-56x+112x-49)-(64x^2-56x+1000))/8x+7^2

ds/dx=((128x^2-56x-49)-(64x^2-56x+1000)/8x+7^2

ds/dx=(64x^2+951)/8x+7^2

Last edited: